Love, proud, understanding rupiah in the perspective of pancasila and law number 7 of 2011 concerning currency - Ayang Fristia Maulana; Pringgo Angga Wijaya; Asnawi Asnawi; Dian Samudra; Mochammad Novel (Trigin Publisher, 2023)
Bank Indonesia is a state institution authorized to issue legal instruments of payment (rupiah currency). In order to maintain rupiah stability in the payment system sector, in 2022 Bank Indonesia will seek to disseminate information about love, pride and understanding of the rupiah to all elements of society. Rupiah currency must be cared for and cared for in 5 ways, namely: May not be folded, May not be scribbled on, May not be clamped, May not be wrinkled, and May not be wetted. This writing method uses normative juridical by using 2 conceptual approaches, namely the statutory approach or also known as the